Stress and stress management in European crisis managers. Issue 1 (3rd May 2016) - Haus, Mirjam; Adler, Christine; Hagl, Maria; Maragkos, Markos; Duschek, Stefan
Abstract : Purpose: – The purpose of this paper is to examine specific stressors and demands, perceived control, received support and stress management strategies of crisis managers (i.e. executives and supervisors of organizations involved in disaster response) in the context of large-scale missions. Design/methodology/approach: – Totally, 31 semi-structured interviews with crisis managers were conducted in five European countries and analyzed with the qualitative text analysis method GABEK®. Findings: – The sample reported high demands and various sources of stress, including event-specific stressors as well as group specific, occupational stressors such as responsibility for decision making, justification of failures or dealing with press and media. While possibilities for control were perceived as limited during large-scale missions, organizational and peer support played an important role in mitigating mission-related stress. Effective stress management strategies were reported as crucial to ensure successful crisis management, and a need for more comprehensive stress management trainings was emphasized. Originality/value: – While stressors and coping strategies in first responders and emergency services personnel have been previously examined, corresponding research regarding the professional group of crisis management leaders remains scarce. Therefore, this study makes an important contribution by examining influential stressors within the work environment of crisis managers and by identifying starting points and requirements for stress management trainings and psychosocial support programs.